CORRELATION BETWEEN PRONATED FOOT AND PELVIC INCLINATION, FEMORAL ANTEVERSION, QUADRICEPS ANGLE AND TIBIAL TORSION (International Journal of Physiotherapy, 2017)
Background: A pronated foot can produce changes in the lower limb kinetic chain. This can affect the gait and increase energy expenditure. However, the relationship between pronated foot and other static alignment factors remains poorly understood. Hence, the objective was to correlate pronated foot with pelvic inclination, femoral anteversion, Q-angle and tibial torsion.Method: An observational study was performed on 60 subjects in the age group of 18-30 years with a BMI of not more than 30. Foot Posture Index was performed on the subjects, and people with a score of +6 or more were selected. Pelvic inclination, femoral anteversion, Q-angle and tibial torsion were measured. Correlation between the Foot Posture Index score and the above four static alignment factors was done using Graph Pad Prism 7 (Pearson’s correlation coefficient and Spearman’s correlation coefficient).Results: There was no significant correlation between Pronated foot and Pelvic inclination (r-value = 0.03309, p-value = 0.8018), Pronated foot and Femoral anteversion (r-value = 0.2185, p-value = 0.0934) Pronated foot and Q-angle (r-value = 0.1801, p-value = 0.1685), Pronated foot and Tibial torsion (r- value = -0.1285, p-value = 0.3277).Conclusion: There is no significant correlation between foot pronation and pelvic inclination, femoral anteversion, Q-angle and tibial torsion. However, the correlation between these factors cannot be completely ignored, and thus, further studies and literature are required to prove the same.